2013
DOI: 10.1002/lt.23724
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass predicts outcomes following liver transplantation

Abstract: Background and aims For patients with end-stage liver disease commonly used indices of nutritional status (i.e. body weight and BMI) are often inflated due to fluid overload (i.e. ascites, peripheral edema) resulting in an underdiagnosis of malnutrition. As muscle is the largest protein reservoir in the body, an estimate of muscle mass may be a more reliable and valid estimate of nutritional status. Methods Therefore, we used pre-transplant computerized tomography data of 338 liver transplant (LTX) candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
225
6
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(245 citation statements)
references
References 16 publications
7
225
6
7
Order By: Relevance
“…The prevalence greatly depended on the definition used. All studies that reported the prevalence of sarcopenia separately for males and females reported a higher prevalence among males (12,14,17,(21)(22)(23)(24)(25)(26)30).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence greatly depended on the definition used. All studies that reported the prevalence of sarcopenia separately for males and females reported a higher prevalence among males (12,14,17,(21)(22)(23)(24)(25)(26)30).…”
Section: Resultsmentioning
confidence: 99%
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 We also hypothesized that testosterone could be a reason for our finding that muscle mass was associated with mortality in men but not in women. Having demonstrated in their own work an association between testosterone and mortality in liver disease, Grossmann et al bring these issues more to light.…”
Section: To the Editorsmentioning
confidence: 97%